(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2013)
A few plants of the Glaucium flavum were found out in July 2012 on the territory of the National park «Tuzlivski lymany». This is the European-Mediterranean species, which is distributed on the north border of natural habitat, included in the Red book of Ukraine. This species was not found before on the territory of the Odessa region. The plants grew on a sandy area, covered large cockleshells, between lake Shagany and lake Small Sasyk.